Management of the Memorization Learning of the Qur'an at Senior High School (SMA) Science Plus Baitul Qur'an Boarding School, Sragen - Saputra, Cefrian Rilasada; Muharrom, Fauzi (Pascasarjana IAIN Kudus, 2023)
The research problem formulation is how is the management of learning to memorize the Qur’an at SMA Science Plus Baitul Qur'an Boarding School Sragen. This type of research is a field with qualitative methods. They are collecting data through observation, interviews, and documentation. The data analysis method uses data reduction, data presentation, and data verification. The research results showed that the Implementation of the Al-Qur'an Memorization Program at Sragen Science Plus Baitul Qur'an Boarding School High School has been going quite well, namely: 1). Judging from the Tahfidz al-Qur'an teacher guiding their students in memorizing the Qur'an, it is guided by the standard operating procedures (SOP) in schools, and the implementation of memorization learning management in its implementation is based on the elements of implementing learning management which consists of elements of POAC (planning, organizing, actuating, and controlling), so that the activities in SMA Science Plus Baitul Qur'an Boarding School Sragen have gone well. The aspect that hindered the implementation of the Al-Qur'an memorization program at the Baitul Qur'an Boarding School Sragen Science Plus High School was that several tahfidz teachers moved so that the halaqah had to be changed, and students felt lazy and skipped. The solution to this problem is to replace teachers who have the same competence, provide rewards and punishments to motivate students to be more enthusiastic about memorizing and find the root of the problem.Manajemen Pembelajaran Menghafal Al-Qur’an di SMA Science Plus Baitul Qur’an Boarding School Sragen. Perumusanmasalahpenelitianadalah bagaimanamanajemen pembelajaranmenghafalal-Qur’andiSMA Science Plus Baitul Qur’an Boarding School Sragen.Jenisrisetiniadalah lapangandengan metode kualitatif.Carapengumpulaninformationmelalui observasi,wawancaradandokumentasi.Metodeanalisisdata yaitu memakai reduksi information, penyajian information,sertaverifikasiinformation.HasilrisetyangdiperolehbahwaPelaksanaan Program Menghafal Al-Qur'an di SMA Science Plus Baitul Qur’an Boarding School Sragensudah berjalan dengan lumayan baik, yaitu: 1). Dilihat dari guru Tahfidz al-Qur'anmembimbingsiswanyadalammenghafalkanal-Qur'ansudahberpedomanpadastandar pedoman(StandardOperatingProcedure;SOP)yangadadisekolahdanpelaksanaanmanajemen pembelajaranmenghafaldalampelaksanaannyasudahberlandaskanpadaunsurpelaksanaan manajemen pembelajaranyangterdiridari unsur POAC (planing, organising, actuating, dan controling),sehingga kegiatanyangadapadaSMA Science Plus Baitul Qur’an Boarding School Sragensudahberjalansesuaidenganbaik.Adapun aspek yang menghambat pelaksanaan programmenghafalal-Qur’andiSMA Science Plus Baitul Qur’an Boarding School Sragenialahbeberapa guru tahfidz pindah, sehingga halaqohnya harus diubah, serta siswa/itimbulrasamalas dan bolos. Solusi dari permasalah tersebut adalah mengganti guru yang kompetensinya sama, memberikan reward dan punishment untuk memotivasi siswa/i agar lebih semangat dalam menghafal. Serta mencari akar permasalahannya.